APPLICATION OF ECONOMIC CONFIDENCE ESTIMATION - Valeriy S. Ayzatullen; Nikolai D. Koryagin (Статистика и экономика)
The socio-economic category of “trust” is studied in the article. The analysis of the existing views about the term “trust” was conducted. A model of the interaction of “Power - Business - People”, using the concept of “trust”, was made. The application and the structure of confidence estimations in economy and politics are studied. The accumulated experience of application of confidence estimations in the macroeconomics of the major countries of the world was showed. The current weaknesses of the confidence indexes are reflected.